2016
DOI: 10.1016/j.clinph.2015.02.054
|View full text |Cite
|
Sign up to set email alerts
|

Discrepancy between perceived pain and cortical processing: A voxel-based morphometry and contact heat evoked potential study

Abstract: This finding suggests that the discrepancy between pain ratings and the amplitude of evoked potentials is not solely related to measurement artifact, but rather attributable, in part, to anatomical differences between subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 47 publications
2
12
0
Order By: Relevance
“…As is evident in Figure 4, even a low number of stimulations (10) yield a larger and reliable vertex waveform, particularly at higher baseline temperatures. This is in line with previous CHEPs studies (Kramer et al, 2013(Kramer et al, , 2016, and was further demonstrated in our own comparison between N2 latencies calculated from 10 stimuli to 20 stimuli, respectively. However, compared to other forms of noxious stimulation (e.g., laser), evoked potentials arising from contact heat stimulation are less synchronized and subject to greater temporal dispersion and higher latency jitter (variability in latency among averaged trials) (Granovsky et al, 2008).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…As is evident in Figure 4, even a low number of stimulations (10) yield a larger and reliable vertex waveform, particularly at higher baseline temperatures. This is in line with previous CHEPs studies (Kramer et al, 2013(Kramer et al, , 2016, and was further demonstrated in our own comparison between N2 latencies calculated from 10 stimuli to 20 stimuli, respectively. However, compared to other forms of noxious stimulation (e.g., laser), evoked potentials arising from contact heat stimulation are less synchronized and subject to greater temporal dispersion and higher latency jitter (variability in latency among averaged trials) (Granovsky et al, 2008).…”
Section: Discussionsupporting
confidence: 93%
“…Irrespective of the baseline temperature, the target peak stimulation intensity was set to 52 • C. The different baseline temperature conditions are displayed in Figure 1. For each condition, 10 stimulations (Kramer et al, 2013(Kramer et al, , 2016 were applied with an 8-12 s inter-pulse interval (Jutzeler et al, 2016;Rosner et al, 2018). A low number of stimulations was used to avoid peripheral sensitization caused by repetitive cutaneous stimulation.…”
Section: Contact Heat Stimulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Subjects were asked to relax and evaluate the intensity of the painful heat stimulation for five stimuli in each task with a visual analogue scale (VAS), in which 0 represented ‘not painful’ and 10 represented ‘an intensity that subjects were unable to tolerate’. In order to familiarize subjects and limit the startle effect, individuals were exposed to contact heat stimuli prior to the acquisition of evoked potentials, as described previously (Kramer et al., ). Under the Hot condition, the thermode baseline temperature was also set at 30, 35 and 40 °C tasks, respectively, and the heat pulse was delivered from each baseline temperature to 46 °C.…”
Section: Methodsmentioning
confidence: 99%
“…Its main characteristic is the progressive increase in temperature, which, in the most conventional stimulation protocols 3 reaches the predetermined peak after some 300 ms. It is known that the time that receptors are exposed to a stimulus and the composition of the stimulus-induced afferent volley are important aspects for the processing of sensory inputs at the central nervous system 6,18,19 . In the study presented here, we have examined the effects of changes in the total time of exposure and energy of the stimulation on physiological, behavioral and cognitive responses.…”
Section: Discussionmentioning
confidence: 99%